2018
DOI: 10.1002/app.46997
|View full text |Cite
|
Sign up to set email alerts
|

Recent advance in antibacterial activity of nanoparticles contained polyurethane

Abstract: Polyurethanes (PUs) are among the most widely used polymers with various applications in several industries. Antibacterial activity is an important feature of PU materials used in medical or many other related consumer products. They can, however, be easily colonized by bacteria and fungi, which may cause many problems for human health. It is therefore very important to enhance the antimicrobial properties of PUs, besides improving their chemical and physical properties. The incorporation of some antibacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 135 publications
0
22
0
Order By: Relevance
“…The mode of antibacterial action of AgNPs is still not resolved [23] though many mechanisms incorporate the release of silver ions while some report formation of pits in the cell wall due to the nanoparticles accumulation [24]. It was reported that the mode of action is size-dependent: the bactericidal effect of AgNPs smaller than 10 nm is due to the nanoparticles, but the predominant mechanism of the larger ones might be the release of silver ions [25].…”
Section: Introductionmentioning
confidence: 99%
“…The mode of antibacterial action of AgNPs is still not resolved [23] though many mechanisms incorporate the release of silver ions while some report formation of pits in the cell wall due to the nanoparticles accumulation [24]. It was reported that the mode of action is size-dependent: the bactericidal effect of AgNPs smaller than 10 nm is due to the nanoparticles, but the predominant mechanism of the larger ones might be the release of silver ions [25].…”
Section: Introductionmentioning
confidence: 99%
“…To protect the material from bacterial attack, different approaches have been followed. One of the useful ways is to enhance antibacterial properties by using different metal oxides nanoparticles with the proper material [ 84 ]. ZnO has also been used in PU/ZnO nanocomposites to enhance antibacterial properties [ 84 ].…”
Section: Pu/zno Composite Applicationsmentioning
confidence: 99%
“…One of the useful ways is to enhance antibacterial properties by using different metal oxides nanoparticles with the proper material [ 84 ]. ZnO has also been used in PU/ZnO nanocomposites to enhance antibacterial properties [ 84 ]. It is common knowledge that a pristine PU material has negligible antibacterial properties [ 35 , 84 ]; however, with the inclusion of ZnO in the PU, the antibacterial properties improve significantly.…”
Section: Pu/zno Composite Applicationsmentioning
confidence: 99%
See 2 more Smart Citations